Effects of Storage Duration and Temperature on the Values of Haematological Parameters in Bovine and Ovine Blood Samples - KIRMIZIGUL, A. H.; GOKCE, E.; SOZMEN, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of the present study was to determine the alterations in haematological values at 0, 12, 24, 36, 48, 60, 72, 84 and 96 hours of storage in bovine and ovine venous blood samples stored at 4˚C and 24˚C in EDTA-coated tubes. Twenty healthy animals, including ten 4-year-old cattle and ten 2-year-old sheep constituted the study material. Bovine blood samples stored at 4˚C produced reliable results for the WBC, RBC, Hb, PCV, MCV, MCH and MCHC levels with the exception of PLT level as PLT levels decreased when the PLT stored 24 hours or longer times. On the other hand ovine blood samples stored at 4˚C for 24 hours or longer, all the parameters measured (WBC, RBC, Hb, PCV, MCV, MCH, MCHC and PLT levels) gave reliable results indicating that ovine blood parameters can be used effectively and safely. Furthermore, in the bovine blood samples, MCHC levels were decreased as from 60 hours stored at 24°C and WBC levels were decreased in the ovine blood samples stored 48 hours or longer at 24°C. However, the blood samples stored at 24°C, the measurement of the RBC, Hb, PCV, MCV, MCH and PLT levels produced reliable results.